Ծագմամբ արմատական ձևույթներով բայերի արժույթը՝ ըստ ներքերականական արտահայտության - Սիլվա Մուրադյան (ՀՀ ԳԱԱ հրատ.)
В глагольном образовании в часности принимают участие արկ, հար, վար, առ, ած, կալ, բան, գույն, միտ, կից морфемы. Глаголы с отглагольными морфемами (արկ, առ, ած, հար, վար), сохраняя лексико-граматические связи с исходным глаголом, образуют как минимум одновалентные глаголы действительного залога. А морфемы, полученные от именных корней (բան, գույն, կից, միտ), образуют глаголы и действительного, и нейтрального залогов. Эти глаголы выражают разные внутриграмматическые значения. The ‘արկ, հար, վար, առ, ած, կալ, բան, գույն, միտ, կից’ morphemes are most commonly used in verb formation. The morphemes (արկ, հար, վար, առ, ած) that have verbal origins preserve the lexicogrammatical links with the verbs they have derived from, and form at least monovalent transitive verbs; whereas the morphemes (բան, գույն, կից, միտ) that have nominal origin, form both transitive monovalent verbs and intransitive avalent verbs. These verbs express various intragramatical relations inside the verb.
Keywords: Philology; Linguistics; Language and Literature